Engineered Exosome‐Based Senolytic Therapy Alleviates Stroke by Targeting p21+CD86+ Microglia - Jialei Yang; Shipo Wu; Miao He (Exploration)
ABSTRACT Stroke remains the leading cause of neurological mortality and disability worldwide, with post‐stroke inflammation significantly hindering neural repair. Despite its critical impact, mechanism‐based therapeutic strategies are scarce. In this study, we uncovered a critically important yet previously unexamined cell population, p21+CD86+ microglia, which accumulated in ischemic region. Unexpectedly, we discovered that p21 interacted with C/EBPβ, driving C/EBPβ‐dependent transcription and upregulating key pro‐inflammatory factors such as Il6, Il1β, Cxcl2, and Cxcl10. To specifically target and eliminate these pathogenic p21+CD86+ microglia, we engineered exosomes with a peptide that selectively binds CD86+ microglia and loaded them with the senolytic Quercetin. Furthermore, we developed an optimized, stable Que@micro‐Exo therapeutic formulation. Systemic administration of Que@micro‐Exo robustly reduced p21+CD86+ microglia and suppressed their pro‐inflammatory phenotype. Notably, functional analyses revealed that Que@micro‐Exo treatment mitigated blood‐brain barrier disruption, promoted beneficial microglial polarization, decreased neutrophil infiltration, and significantly enhanced functional recovery following cerebral ischemia, all with a favorable safety profile. Our preclinical findings lay the foundation for targeting p21+CD86+ microglia as a novel therapeutic strategy, highlighting the potential of exosome‐based senolytic anti‐inflammatory therapy for stroke and other central nervous system disorders.